Teknisen ohjeen suoja liikesalaisuusdirektiivin valossa - Mylly, Ulla-Maija (Lakimies, 2024)
Protection of technical instructions in the light of the Trade Secrets Directive The article analyses Finland’s implementation of the EU’s Trade Secrets Directive (TSD). The focus is on analysing whether Finnish protection of technical instructions conflicts with the harmonisation objective under the TSD for the protection of trade secrets. The protection of technical instructions covers information when it is not publicly available and when technical instructions have been entrusted to a party to complete work or a task or otherwise in a business relationship. The problem with this protection is that the requirements for protection are not in line with those required for trade secrets. The most important difference is that a party does not need to take reasonable steps to keep information secret to receive protection for entrusted technical instructions. Consequently, the protection is given more easily, but the remedies under the Finnish trade secrets act are the same as those provided for trade secrets. The article analyses this conflict in the light of the EU pre-emption doctrine. The article includes a step-by-step analysis of the scope overlap between the protection of trade secrets and technical instructions and why the less strict requirements for protection conflict with the harmonisation objective of the TSD. The article concludes that Finnish legislation on technical instructions should be amended due to the conflict.